Pseudohypoaldosteronism type 1 and Liddle’s syndrome mutations that affect the single-channel properties of the epithelial Na+ channel - Boiko, Nina (John Wiley & Sons, Ltd, 2015)
These studies test whether three disease-causing mutations in genes (SCNN1A and SCNN1G) encoding subunits of the epithelial Na+ channel, ENaC, affect the biophysical and gating properties of this important renal ion channel. The S562P missense mutation in αENaC and the K106_S108delinsN mutation in γENaC are associated with pseudohypoaldosteronism type 1 (PHA1). The N530S missense mutation in γENaC causes Liddle’s syndrome. Incorporation of S562P into αENaC and K106_S108N into γENaC resulted in significant decreases in macroscopic ENaC currents. Conversely, incorporation of N530S into γENaC increased macroscopic ENaC current. The S562P substitution resulted in a nonfunctional channel. The K106_S108N mutation produced a functional channel having a normal macroscopic current–voltage relation, there was a slight but significant decrease in unitary conductance and a marked decrease in single-channel open probability. The N530S substitution increased single-channel open probability having no effect on the macroscopic current–voltage relation or unitary conductance of the channel. These findings are consistent with mutation of residues at 562 in αENaC and 530 in γENaC, and a 3′ splice site in SCNN1G (318-1 G→A; K106_108SdelinsN) resulting in aberrant ENaC activity due to changes in the biophysical and gating properties of the channel. Such changes likely contribute to the cellular mechanism underpinning the PHA1 and Liddle’s syndrome caused by these mutations in ENaC subunits.